Determining the mood in the lyrics of famous modern artists - Zanchak Maria; Vysotska Victoria (онлайн, 2022)
The article aims to compare the moods in the lyrics of famous modern artists of various genres (from pop to rap) and to understand what emotions dominate in the lyrics that listen to modern youth. The lyrics of three famous artists were chosen for this: Taylor Swift (due to his significant influence on pop culture in general), BTS (due to their significant influence on young people around the world), and Eminem (as a cult representative of rap culture).